Morfoanatomia e ultraestrutura de sementes e plântulas de palmeiras do cerrado - Hellen Cássia Mazzottini dos Santos (2017)
The Cerrado contains more than 50 described species of palm trees that, due to the unique characteristics of this biome, possess intriguing adaptive characteristics. Among these is seminal dormancy and large amounts of reserve compounds. The embryo is linear, possessing a microscopic axis within the cotyledonary petiole and a distal portion that is differentiated into a highly specialized haustorium, which is a structure involved in the mobilization of endospermic reserves for the growing seedling; however, information about how this process occurs is still incipient. This work evaluates the physiology, anatomy, cytochemistry and ultrastructure of the seeds of three economically important Neotropicalpalm species. The first chapter aims to address the effect of the components of the operculum on the germination of Acrocomia aculeata, Attalea vitrivir and Butia capitata, as well as the effect of inhibition, cultivation time and the application of gibberellic acid (GA3) on embryonic growth and the structure of micropylar endosperm. The level of dormancy was found to increase among the seeds A. vitrivir, B. capitata and A. aculeata, with A. aculeata having a greater degree of resistance to displacement of the operculum. The seeds of A. vitrivir and A. aculeate experience embryonic growth that is directly related to the displacement of the operculum, whose resistance, in the three studied species,decreases with imbibition, is not influenced by GA3 and is not related to the activity of endo--mannanase. Although the mechanical effect of embryonic growth is determinant, the pectic profile of the median lamella in the line of weakness of the micropylar endosperm and the remodeling of the cell wall, which differ among the studied species, can be considered important components of the control of germination in palm seeds. The second chapter involves the definition of developmental stages for seedlings of A. aculeata and the elucidation of the roles of the haustorium and endosperm during mobilization of reserves. Reserves mobilization begins in the haustorium during germination and subsequently occurs in the endosperm adjacent to the haustorium, gradually forming a digestive zone. The first compounds to be mobilized are proteins and polysaccharides, followed by lipids and cell wall components. The haustorium activates and controls mobilization, forming transitory reserves and translocating them to the vegetative axis; theendosperm has an active role in serving as a site of intense enzymatic activity associated with protein bodies. The development of seedlings of A. aculeata can be described to have six phases that occur over approximately 150 days, a process that exhibits alternationbetween stages of accumulation and consumption of haustorium reserves. The third chapter aimed to describe cellular variation related to the mobilization of embryonic and endospermic reserves during germination and the initial development of seedlings of A.aculeata. The haustorium was found to contain lipid bodies associated with glyoxysomes and proteinaceous vacuoles, which are organelles involved in lipid mobilization. The pattern of mobilization of endosperm is similar to that of the haustorium, but there is no evidence of direct involvement of organelles; the carbohydrates in the wall hydrolyze andthe cells lose their integrity and accumulate around the haustorium. The haustorium does not possess cytological characteristics indicative of a function of secreting enzymes that act on the endosperm, but it is a structure that has the initial function of reserve storage andplays a role in the absorption and storage of transient reserves throughout the establishment of the seedling. The endosperm has storage and self-degradation functions, with hydrolytic enzymes and products of hydrolysis being transported via apoplast